Teaching acid-base theories in the era of disinformation: A systematic review with proposals for content integration - dos Santos Silva, Erasmo Moises; Arroio, Agnaldo (Eclética Química, 2025)
This paper is rooted in the premise that addressing scientific disinformation and misinformation about acid-base theories requires a multidisciplinary approach, approximating acid-base knowledge with content typically not addressed in chemistry classes. Stemming from this principle, this paper analyzes how peer-reviewed publications for chemistry teaching approach the representation of acid-base theories in the context of informational disorders (disinformation and misinformation) through a literature review and textual analysis. The papers analyzed address cases of informational disorders through a disciplinary lens, with a pronounced emphasis on resorting to acid-base contents to debunk erroneous messages, even though the contexts explored reference socioscientific issues. As a response, this paper broadens the conservation, by proposing other contents that could convey the nature of science as well, the functioning of traditional and modern media, and values and ideologies. By doing so, this paper provides more elements for critical and broader readings of acid-base theories in informational disorders, elevating chemistry teaching to better address contemporary challenges arising from the interplay between science and media.